The name as a distinctive of the identity and characterization of the person in the tradition «El padre Pata» by Palma - Rodríguez Chávez, Iván (2022)
Ricardo Palma’s tradición (tradition) «El padre Pata» (father Foot) is used in this essay, from a literature stance, to identify and explain the legal nature of a person’s name and its direct relationship with the identity and persona of an individual, as well as how altering a name affects the individualization of a subject of law within a society. The text is analyzed from a literature and legal perspective, and it’s seen as a case subject to study in the light of current civil law. Its value shall be the result of the application of doctrinal interpretation of norm and theory.